Simulation of transaction malleability attack for blockchain-based e-Voting. (May 2020) - Khan, Kashif Mehboob; Arshad, Junaid; Khan, Muhammad Mubashir
Abstract: Blockchain has been adopted to address significant challenges, such as trust in diverse domains, including voting, logistics and finance. However, transaction malleability has been identified as a threat for blockchain, which can potentially lead to an inconsistent state that can result in further attacks such as double-spending. In this context, this paper is focused on investigating the feasibility of transaction malleability within a typical blockchain application aiming to identify scenarios that may lead to a successful transaction malleability attack. Our objective in doing so is to highlight conditions which cause such attack to facilitate the development of protection mechanisms for them. Specifically, this paper presents a successful simulation of transaction malleability attack within the context of blockchain-based electronic voting. The evaluation has identified the impact of parameters, such as network delay and block generation rate in achieving a successful transaction malleability attack, which highlights future directions of research.